2020
DOI: 10.1089/neu.2019.6471
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State fMRI Metrics in Acute Sport-Related Concussion and Their Association with Clinical Recovery: A Study from the NCAA-DOD CARE Consortium

Abstract: There has been a recent call for longitudinal cohort studies to track the physiological recovery of sport-related concussion (SRC) and its relationship with clinical recovery. Resting-state functional magnetic resonance imaging (rs-fMRI) has shown potential for detecting subtle changes in brain function after SRC. We investigated the effects of SRC on rs-fMRI metrics assessing local connectivity (regional homogeneity; REHO), global connectivity (average nodal strength), and the relative amplitude of slow oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 70 publications
4
45
0
Order By: Relevance
“…Taken together, altered recruitment of the right MFG after mTBI may represent an over-arching disruption in modulating attention. These findings are also consistent with resting-state fMRI studies in concussion and mTBI, which have observed altered functional connectivity in the right MFG (Meier et al., 2019) as well as other regions that mediate internally-oriented processes (Zhu et al., 2015; Militana et al., 2016; Borich et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, altered recruitment of the right MFG after mTBI may represent an over-arching disruption in modulating attention. These findings are also consistent with resting-state fMRI studies in concussion and mTBI, which have observed altered functional connectivity in the right MFG (Meier et al., 2019) as well as other regions that mediate internally-oriented processes (Zhu et al., 2015; Militana et al., 2016; Borich et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Our results of initial increased functional connectivity associated with significant motor-balance deficits were consistent with some smaller studies that showed significant rsfMRI changes associated with post-concussion symptoms [ 34 , 36 , 37 , 102 ]; the trends and networks most frequently involved in studies were reduced connectivity in the posterior DMN [ 34 , 102 ], increased connectivity in the anterior DMN [ 34 , 102 ], reduced anti-correlation among networks with anti-correlation relationships [ 102 ], and decreased local intrinsic functional connectivity in the SN [ 36 , 37 ], in the lateralised cognitive control network [ 37 ], and in regions related with motor, sensorimotor, attention, and phonological processing [ 36 ]. On the other hand, Meier et al reported short-term elevated local intrinsic functional connectivity in regions associated with the DMN that normalised upon symptom recovery [ 39 ]. Other studies in humans have also found persistent rsfMRI changes beyond symptom recovery [ 35 , 103 , 104 ], with one study reporting no significant changes to rsfMRI connectivity when symptoms were highest, but ongoing rsfMRI changes after symptoms had recovered [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…At 8 days post-injury, a global increase in functional connectivity was seen with improving symptoms, which recovered by 15 days post-injury [ 38 ]. Similarly, Meier et al reported increased local intrinsic functional connectivity in the right middle and superior frontal gyri at 24–48 h post-injury, which were normalised at 7 days and 6 months post-medical-clearance [ 39 ]. To the best of the authors’ knowledge no functional imaging study combining stimulus-evoked functional MRI and rsfMRI were published in a mouse model of closed-head injury.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, adult studies have also reported decreased thalamic fALFF 23 days postinjury, 46 region-dependent increases and decreases acutely, 47 or null findings in fALFF in a relatively large cohort of adult athletes with acute concussion. 15 These discrepancies could be due to differences in age, injury mechanism, or time since injury between the studies, all of which likely affect BOLD imaging metrics postinjury. 16 Of particular relevance, inconsistencies between our findings and prior adult studies could also be explained by the dynamic and highly plastic nature of the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, they do not require multiple corrections for familywise error if looking across multiple regions and may better account for the heterogeneous nature of mTBI at the local level. Although previous studies have examined ReHo and fALFF alterations in both sport and emergency department (ED) samples of adult mTBI patients, 8,14,15 there is a lack of data using these parameters to characterize the effects of mTBI in children. 16 The first aim of our study was to examine whether ReHo or fALFF were affected and subsequently recovered in a large cohort of pmTBI at subacute (SA;~1 week) and early chronic (EC;~4 months) postinjury periods relative to age-and sexmatched healthy controls (HCs).…”
mentioning
confidence: 99%